2006
DOI: 10.1002/app.22558
|View full text |Cite
|
Sign up to set email alerts
|

Polycarbonate microfilters by nuclear tracking and chemical etching (track‐etching) technique: Preparation and characterization

Abstract: Track-etched polycarbonate (PC) microfilters were successfully prepared by tracking with fission fragments in the Thai Research Reactor-1/Modification-1 nuclear reactor and chemical etching with sodium hydroxide aqueous solutions. The porosity of the as-prepared microfilters can be controlled by varying the exposure time in the nuclear reactor and the average pore diameter by varying the etching conditions. In the present work, the average pore diameter of the as-prepared microfilters ranged from ϳ2.0 to 9.5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…It was found that nitrogen drying usually creased the filters. This method of increasing sizes is presumably similar to that used in commercial manufacture (Makphon et al , 2006).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that nitrogen drying usually creased the filters. This method of increasing sizes is presumably similar to that used in commercial manufacture (Makphon et al , 2006).…”
Section: Methodsmentioning
confidence: 99%
“…To improve the pore trapping technique, we have determined cell size by dynamic light scattering and then etched commercially available PCTE filters (Makphon et al , 2006) to a better size for trapping, making the method more effective and potentially applicable to a wider range of strains and species. This study has used S. aureus (NCTC 8532) as a model gram‐positive coccus to demonstrate the method for improvement of bacterial pore trapping.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in pore densities are known to depend on times of irradiation and pore diameters are the effects of etching time and concentrations of the etchants [5]. Based on the availability of nuclear reactor, membranes prepared using thermal neutron flux to produce fission fragments for generating the latent tracks have been reported [6][7][8]. However, the fast neutron was observed to provide better results in pore piercing compared to thermal neutron bombardment but high pressure of water flux was required [8].…”
Section: Introductionmentioning
confidence: 99%
“…Track etching 1 is a well-known technique for making pores in various materials such as polyesters, 2 nylons, 3 polycarbonate membrane 4,5 and glass. 6,7 Tracking is usually performed by irradiating substrates with heavy ions accelerated to $15% the speed of light using a linear particle accelerator.…”
Section: Introductionmentioning
confidence: 99%